Bioinspired Surfaces: Bioinspired Functional Surfaces Enabled by Multiscale Stereolithography (Adv. Mater. Technol. 5/2019). Issue 5 (10th May 2019) - Li, Yuanrui; Mao, Huachao; Hu, Pan; Hermes, Mark; Lim, Haneol; Yoon, Jongseung; Luhar, Mitul; Chen, Yong; Wu, Wei
Abstract : Two light beams with different colors indicate there are two lasers of different wavelengths in the 3D printer to improve printing efficiency, as presented in article number1800638 by Wei Wu and co‐workers. The denticle array being printed by the lasers is the structure printed in this work and was inspired by shark skin texture with fluid drag reduction function.